The Concept of Independent Learning to Stimulate Creativity of Early Children: A Study of Ki Hajar Dewantara’s Philosophy - Marwany Marwany; Besse Nirmala; Suyitno Muslim (STAI Hubbulwathan Duri, 2023)
The Indonesian people's low creativity index greatly affects the quality of education, starting from the Early Childhood Education (ECE) level to the tertiary level. This study aims to describe the concept of independent learning to stimulate early childhood creativity in the study of Ki Hajar Dewantara's philosophy. This study uses library research to explore the concept of independent learning that is relevant according to the philosophy of Ki Hajar Dewantara. This research method is qualitative, using a descriptive approach. The data collection technique is content analysis with deductive and comparative thinking methods. The results showed that the concept of independent learning, according to Ki Hajar Dewantara's philosophy, was very supportive in stimulating the creativity of early childhood. The concept of independent learning is very suitable to stimulate children's creativity based on the principles of forging, loving, honing, and fostering as well as the tri-N idea (niteni, nirokke, and nambahi). The concept of the Among system education is that the nature of nature is a condition for reviving and achieving progress as quickly as possible, and independence is a condition for restoring and moving children's inner and outer strength so that they can live independently.